Audiological findings in presbycusis - Punnan BT (Journal of All India Institute of Speech and Hearing, 1970)
Increasing deafness in the aged is one of the interesting chapters and psychologically perhaps the most important in our Bible of Audiology. Aging is the p·rocess of growing mature or old - occurs in all cells and structures of the body